2015
DOI: 10.1086/678983
|View full text |Cite
|
Sign up to set email alerts
|

Early Childbearing, Human Capital Attainment, and Mortality Risk: Evidence from a Longitudinal Demographic Surveillance Area in Rural KwaZulu-Natal, South Africa

Abstract: Using a rich longitudinal dataset, we examine the relationship between teen fertility and both subsequent educational outcomes and HIV related mortality risk in rural South Africa. Human capital deficits among teen mothers are large and significant, with earlier births associated with greater deficits. In contrast to many other studies from developed countries, we find no clear evidence of selectivity into teen childbearing in either schooling trajectories or pre-fertility household characteristics. Enrolment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 46 publications
2
45
0
Order By: Relevance
“…Late adolescence, in particular, appears a 'critical period' to promote enrolment or retention with implications for health across the life course [67]. During late adolescence, people develop new behavioural patterns; they acquire new skills [3]; they make their own decisions for the first time; and many of these decisions have particularly high path dependence, including pregnancy [68]. Investments in schooling during this period could improve health and engender adolescents' capabilities to lead fulfilling lives [69], especially since we see a substantial fall-off in school enrolment after age 15.…”
Section: Discussionmentioning
confidence: 99%
“…Late adolescence, in particular, appears a 'critical period' to promote enrolment or retention with implications for health across the life course [67]. During late adolescence, people develop new behavioural patterns; they acquire new skills [3]; they make their own decisions for the first time; and many of these decisions have particularly high path dependence, including pregnancy [68]. Investments in schooling during this period could improve health and engender adolescents' capabilities to lead fulfilling lives [69], especially since we see a substantial fall-off in school enrolment after age 15.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of rural KwaZulu‐Natal, South Africa, PopPov‐supported research by Ardington and colleagues found that teen mothers (younger than age 20) had worse educational and health outcomes than their peers who did not have a teen birth . Moreover, they found that fertility timing matters, with first birth in earlier teen years (under age 17) having more pronounced negative effects on educational outcomes than in later teen years (ages 17‐19).…”
Section: Better Reproductive Health Enables Women's Economic Empowermentmentioning
confidence: 90%
“…In setting these assumptions, we have not attempted to adjust for dropout related to pregnancy, although this is allowed for separately in the model (see section 3.5.4). However, pregnancy is not expected to have a major impact on average rates of dropout in girls, because most girls return to school after their pregnancy [82, 87, 88]. This is verified in the model calibration (section 3.5.8), which suggests that only about 15% of girls who drop out of school permanently do so because of pregnancy.…”
Section: Demographic and Socio-economic Variablesmentioning
confidence: 94%